2019
DOI: 10.1177/0255761419842415
|View full text |Cite
|
Sign up to set email alerts
|

The state of music education in the basic general public schools of Ecuador: The administrators’ perspective

Abstract: This study examines the state of music education in the public schools of Ecuador from the perspective of school administrators. A survey that was distributed to 1800 school administrators (27.4% response rate) was used to answer the following research questions: What are administrators’ perceptions of the current national policies for arts education? What are administrators’ perceptions of the current state of the music curriculum? Is there a difference between administrators’ perceptions of current and ideal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
3
3
0
Order By: Relevance
“…The evaluation performed allows determining the programmes with a higher presence level in the Curricular structure (ECU) in aspects such as the dilemma between Musical or pedagogical emphasis (EMP) in the training of the accredited student, or Higher dedication to music education (MDM) offered by these programs. These results are coherent with the findings of other studies, such as Abril (2019) and Pittau Sevilla (2016), relative to the training focus of music education programs in Latin America and their divergences between the music, pedagogic or artistic focus of the curricular projects.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The evaluation performed allows determining the programmes with a higher presence level in the Curricular structure (ECU) in aspects such as the dilemma between Musical or pedagogical emphasis (EMP) in the training of the accredited student, or Higher dedication to music education (MDM) offered by these programs. These results are coherent with the findings of other studies, such as Abril (2019) and Pittau Sevilla (2016), relative to the training focus of music education programs in Latin America and their divergences between the music, pedagogic or artistic focus of the curricular projects.…”
Section: Discussionsupporting
confidence: 91%
“…f = frequency; % = percentage; Nw = Number of encoded words.emphasis (EMP) in the training of the accredited student, or Higher dedication to music education (MDM) offered by these programs. These results are coherent with the findings of other studies, such asAbril (2019) and PittauSevilla (2016), relative to the training focus of music education…”
supporting
confidence: 92%
“…Similar apprehension about the impact of school accountability systems and the ensuing high-stakes testing on the narrowing of the curriculum has been raised by others, both in the UK (e.g. Bath et al, 2020) and internationally (Abril, 2019;Hentschke, 2013;Hebert & Heimonen, 2013;O'Connor & McTaggart, 2017;Shaw, 2018). The study reported in this article took place before the Covid-19 pandemic which greatly interrupted educational provision more broadly (Pietro et al, 2020) and impacted music teaching and learning in many ways (Daubney & Fautley, 2020, 2021.…”
Section: Introductionsupporting
confidence: 70%
“…During our stay we noticed the absence of learning native songs in the classroom, which means that the musical heritage of the Peruvian Amazon is in danger of extinction. These circumstances, which not only affect Peru but are common in many other countries, are mainly due to the lack of knowledge on the part of the educational authorities about the multiple virtues of musical education in the integral formation of people (Figueiredo, 2010;Lorenzino, 2011;Abril, 2017;Alvarado and Lira-Cerda, 2017). It is urgent that the scientific studies results carried out on this situation be transferred to these authorities so that the necessary adaptations to the current educational policies can be made.…”
Section: Discussionmentioning
confidence: 99%